2020
DOI: 10.1007/s10291-019-0948-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PPP-RTK based on BDS-3/BDS-2/GPS observations: a case study in Europe

Abstract: The Chinese BeiDou Navigation Satellite System (BDS) transited from regional (Asia-Pacific) to global on December 28, 2018. In this study, the performance of PPP-RTK based on BDS-3/BDS-2/GPS observations is analyzed by utilizing the observations in Europe during a calm ionospheric disturbance period with Kp-index ranging from 0o to 2-. Satellite clock offsets are first estimated and then fixed to determine the uncalibrated phase delays (UPDs) and the ionospheric/tropospheric information from the reference netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Because atmospheric augmented PPP AR can achieve fast and reliable positioning performance, which is similar to the positioning and convergence performance of real-time kinematics (RTK), this technology is also called PPP-RTK [11]. Benefiting from the many advantages of PPP-RTK, great efforts have been made to work on PPP-RTK with promising results in recent years [12][13][14][15][16][17][18][19][20][21]. Li et al (2011) performed an atmospheric augmented PPP ambiguity resolution experiment by using atmospheric corrections derived from a network with an average distance of approximately 60 km.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because atmospheric augmented PPP AR can achieve fast and reliable positioning performance, which is similar to the positioning and convergence performance of real-time kinematics (RTK), this technology is also called PPP-RTK [11]. Benefiting from the many advantages of PPP-RTK, great efforts have been made to work on PPP-RTK with promising results in recent years [12][13][14][15][16][17][18][19][20][21]. Li et al (2011) performed an atmospheric augmented PPP ambiguity resolution experiment by using atmospheric corrections derived from a network with an average distance of approximately 60 km.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the global positioning system (GPS) alone can achieve sub-decimeter-level positioning accuracy in both the horizontal and vertical components within 4.5 and 5.0 min-1.0 and 0.5 min for multi-GNSS measurements. Li et al (2020) used GPS/BeiDou navigation satellite system (GPS/BDS) observations to investigate the positioning and convergence performance of PPP-RTK. The results demonstrated that PPP-RTK could be obtained utilizing averages of 1.5, 1.6, and 1.2 epochs, and the root mean squares (RMS) of positioning performance in the north, east, and upwards components were 0.73, 0.98, and 2.97 cm for BDS alone; 0.47, 0.80, and 1.97 cm for GPS alone; and 0.35, 0.56, and 2.33 cm for combined GPS + BDS observations.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars focused on the performance of the combination of QZSS and other GNSS systems [6,[19][20][21], and concluded that the combined positioning of QZSS and other systems achieved a performance gain, especially under the condition of large cut-off angle. In recent years, many scholars have focused on the mathematical model and positioning performance of BDS-2/BDS-3 and GPS [22][23][24][25]. It is found that integrated BDS-2/BDS-3 can achieve significantly better positioning performance than GPS in PPP and RTK.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it is about 10–30 min, in order to achieve centimetre-level positioning accuracy [ 9 ], which limits the high accuracy real-time positioning applications. Although the augmented PPP technique, based on different GNSS and using a dual-frequency satellite receiver, together with local reference stations, significantly shortens the above time to first point [ 10 , 11 ], a local reference station and datalink are necessary. Furthermore, much attention should be paid to ambiguity resolution and validation, which affects the positioning reliability for both RTK and PPP.…”
Section: Introductionmentioning
confidence: 99%